2008
DOI: 10.1007/bf03175557
|View full text |Cite
|
Sign up to set email alerts
|

Comparative approach for detection of biosurfactant-producing bacteria isolated from Ahvaz petroleum excavation areas in south of Iran

Abstract: The current study was undertaken to compare four analytical methods including drop collapse, oil spreading, surface tension (SFT) measurements, and blood agar lysis tests for detection of biosurfactant-producing bacteria. Among 32 biosurfactant-producing bacteria isolated from Ahvaz oil fields, in south of Iran, 16 isolates (50%) exhibited highest biosurfactant production. Eleven isolates (MASH.1 to MASH.11) demonstrated a reduction in surface tension from 65 mN/m to less than 41 mN/m. The results showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Earlier reports on screening of biosurfactant producing microbes discussed either a single method or combination of two or three methods like hemolytic assay, BATH assay, drop collapse method, oil spreading assay and surface tension measurement [20][21][22]. Few reports have 6 to 8 screening methods but with no surface tension measurement.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier reports on screening of biosurfactant producing microbes discussed either a single method or combination of two or three methods like hemolytic assay, BATH assay, drop collapse method, oil spreading assay and surface tension measurement [20][21][22]. Few reports have 6 to 8 screening methods but with no surface tension measurement.…”
Section: Resultsmentioning
confidence: 99%
“…Carrillo et al [36] found an association between hemolytic activity and surfactant production and they recommended the use of blood agar lysis as a primary method to screen biosurfactant production. None of the studies reported in the literature [21][22][23][36][37][38] mention the possibility of biosurfactant production without a hemolytic activity. However, in some studies hemolytic assay excluded many good biosurfactant producers and in some reports strains with positive hemolytic activity were found negative for biosurfactant production [21].…”
Section: Screening For Biosurfactant Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…MASH1 biosurfactant produced by MASH1 (26) using soybean oil as sole carbon source was cultivated in SOM medium composed of (g/L): NaNO 3 . Seed cultures were inoculated (2% v/v) in 250 ml flasks containing 50 ml of production medium followed by incubation at 200 rpm and 30 °C for 6 days.…”
Section: Biosurfactants and Test Microorganismsmentioning
confidence: 99%
“…There appeared several colonies and pure cultures of each morphologically distinct colonies were obtained by repetitive streaking onto solid LB medium. To isolate the strains capable of biosurfactant production, oil spreading method [2,12] and hemolytic activity [13] were applied. Among several bacterial strains isolated, a potent biosurfactantproducing bacterial strain was identified and examined as creation of significant clear zone on the oil surface and maintained on LB agar medium at 4°C for further experiments.…”
Section: Screening and Isolation Of Biosurfactant-producing Bacteriamentioning
confidence: 99%